(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
This article provides information on the ancient history of relations between India and Central Asia and their socio-political status. With the help of this information, the life of the country and the people was studied in concrete figures in order to get a clear idea of the historical processes of that period.